Formation And Development Of Folklore Art In Uzbekistan - M. G’iyosiddinova (Peerian Journals Publishing, 2023)
The article provides information about the history of the formation and development of folklore art in Uzbekistan. Also, in the Kokan khanate, scientific opinions were held about handicrafts and their types: coppersmithing, cart making, cradle making, pest control, carving, military weapon production, ceramics and glassware, artistic textiles, hat making, embroidery, blacksmithing, coppersmithing, etc.
Keywords: folk literature; folklore; practical art; folk dance art